Corrosion mechanisms of Zn(Mg, Al) coated steel: 2. The effect of Mg and Al alloying on the formation and properties of corrosion products in different electrolytes. (January 2015) - Salgueiro Azevedo, M.; Allély, C.; Ogle, K.; Volovitch, P.
Graphical abstract: Highlights: Basic zinc salts (BZS) decrease oxygen reduction rate on galvanized steel and ZnMgAl. With pH increase BZS transforms into ZnO with a loss of the inhibiting effect. Mg 2+ ions delay (at pH 12.5) or suppress (at pH 10) the transformation BZS → ZnO. Al 3+ and Zn 2+ form layered double hydroxides remaining stable at alkaline pH. A residual Al "skeleton" may increase the compactness of the patinas formed on ZnMgAl. Abstract: Oxygen reduction rate on galvanized steel and ZnAlMg coated steel decreased in presence of corrosion products identified as basic zinc salts (BZS) and layered double hydroxides (LDH). Under cathodic polarization of galvanized steel the transformation BZS → ZnO occurred, resulting in a loss of the inhibiting effect. It did not happen on ZnMgAl. Acid–base titrations of Zn 2+ -containing solutions with and without additives demonstrated that (1) Mg 2+ ions delay the transformation BZS → ZnO; (2) Al 3+ forms LDH which remains stable even at pH > 12.5. A residual Al "skeleton" was observed in corrosion products formed on ZnMgAl. It may increase the compactness of the patinas.